Mass Violence and Memory in the Digital Age
XVIII, 246 p. 14 illus.
Keywords: This volume explores the shifting tides of how political violence is memorialized in today's decentralized, digital era. The book enhances our understanding of how the digital turn is changing the ways that we remember, interpret, and memorialize the past. It also raises practical and ethical questions of how we should utilize these tools and study their impacts. Cases covered include memorialization efforts related to the genocides in Rwanda, Cambodia, Europe (the Holocaust), and Armenia; to non-genocidal violence in Haiti, and the Portuguese Colonial War on the African Continent; and of the September 11 attacks on the United States. .